Peran Sistem Keamanan Terhadap Data Pribadi di Platform Digital Dengan Perspektif Diplomasi Siber Dalam Hubungan Internasional - Fathi Ahmad Safaraz (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The purpose of this study is to examine how security systems are responsible for protecting personal data on digital platforms, as well as how the role of security systems is positioned within Indonesia's cyber diplomacy in the international diplomatic arena. This research is motivated by the numerous cases of personal data breaches in Indonesia, including 124 data protection violations from 2019 to 2024, along with 279 million BPJS Health data records, 17 million PLN customer data records, and the fact that the Personal Data Protection Bill and Cyber Security and Resilience Bill have not yet been enacted. Using a qualitative methodology with a case study design, this research incorporates policy document analysis, data breach reports, international regulations such as GDPR, and comparative studies of data protection policies in the European Union, the United States, and Singapore. The findings reveal that Indonesia's digital platform security systems still face significant challenges, as evidenced by the low implementation of technical mechanisms such as encryption and two-factor authentication, regulatory gaps that create a legal vacuum, and a shortage of cybersecurity human resources amounting to 50,000 professionals. In terms of cyber diplomacy, Indonesia lacks a comprehensive diplomatic strategy and tends to be reactive in multilateral forums such as ASEAN and the UN, in contrast to countries like Germany and Singapore that actively promote their data governance models. Furthermore, through the lens of digital dependency theory, this study finds that the failure of national data protection has diminished Indonesia's credibility and bargaining power in the international arena while also reinforcing global cyber governance inequalities.